2021
DOI: 10.1002/advs.202104884
|View full text |Cite|
|
Sign up to set email alerts
|

Multimodal Enzyme‐Carrying Suprastructures for Rapid and Sensitive Biocatalytic Cascade Reactions

Abstract: Colloidal assemblies of mesoporous suprastructures provide effective catalysis in an advantageousvolume-confined environment. However, typical fabrication methods of colloidal suprastructures are carried out under toxic or harmful conditions for unstable biomolecules, such as, biocatalytic enzymes. For this reason, biocatalytic enzymes have rarely been used with suprastructures, even though biocatalytic cascade reactions in confined environments are more efficient than in open conditions. Here, multimodal enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…The double reciprocal Lineweaver-Burk plot in Figure 10 is used to linearize the data of the Michaelis-Menten saturation curves and for more reliable determination of the basic kinetic parameters—the Michaelis-Menten constant K m constant and the maximum velocity V max . Kinetics studies using the same approach have been reported earlier by other authors [ 49 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 76%
“…The double reciprocal Lineweaver-Burk plot in Figure 10 is used to linearize the data of the Michaelis-Menten saturation curves and for more reliable determination of the basic kinetic parameters—the Michaelis-Menten constant K m constant and the maximum velocity V max . Kinetics studies using the same approach have been reported earlier by other authors [ 49 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 76%
“…Porous supraparticles are produced through the self-assembly of primary colloidal particles. The intrinsic properties of various primary colloids can be used as supraparticles providing large surface areas and porosity in confined structures. With the increasing importance of supraparticles in diverse applications such as drug delivery, , diagnostics, photonics, and sensing, , various supraparticle synthesis methods have been proposed. Among different strategies, in recent years, the surface-templated evaporation driven (S-TED) method, which is used to fabricate supraparticles by drying colloidal dispersion drops on liquid-repellent surfaces, has been extensively investigated. , The S-TED process comprises three steps: (i) placing a colloidal dispersion drop on a liquid repellent surface, (ii) drying the solvent in air to form a self-assembled supraparticle, and (iii) collecting the supraparticle from the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis through simple solvent drying of dispersion drops is a key strength of the S-TED method. The composition, size, shape, and porosity of supraparticles can be manipulated easily by means of the S-TED method under mild ambient conditions without using toxic solvents and heat. Therefore, sensitive biomaterials, such as enzymes, can be assembled as supraparticles without significant damage in the process …”
Section: Introductionmentioning
confidence: 99%
“…Over the last few decades, a number of different methods for the immobilization of enzymes on solid surfaces have been developed, as summarized in many review articles. A recent focus is on the immobilization of enzymes for flow-through applications. , Conceptually, the methods for enzyme immobilization on silica surfaces can be grouped into at least three categories: (i) covalent binding to a silica surface using organic linker moieties and a chemical modification of the silica surface, , (ii) noncovalent adsorption on either neat silica or surface-modified silica, , and (iii) entrapment in the pores of porous silica materials. ,, For the methods based on noncovalent enzyme adsorption, three approaches are relevant for comparison to the work presented: (i) layer-by-layer deposition using a charged polymer that has an opposite charge to the overall charge of the enzyme at the pH applied, , (ii) the use of recombinant enzymes carrying His-tags to bind to a silica surface that is surface-functionalized to allow the efficient binding of His, and (iii) the use of recombinant chimeric enzymes containing a polycationic protein module (an arginine-rich mini protein) that binds to unmodified, anionic silica surfaces (“fusion protein approach”). ,, The methodology used in this work is somewhat related to the fusion protein approach, although the use of recombinant enzymes is not required. In our work, the enzyme of interest is immobilized noncovalently on unmodified silica surfaces after several enzyme molecules are first covalently bound to polymer molecules in an aqueous solution. …”
Section: Introductionmentioning
confidence: 99%